2013
DOI: 10.4236/fns.2013.49127
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Whole Coffee Fruit Concentrate Powder on Plasma Levels of Total and Exosomal Brain-Derived Neurotrophic Factor in Healthy Subjects: An Acute Within-Subject Clinical Study

Abstract: A pilot study by Reyes [1] previously showed that ingestion of single dose of whole coffee fruit concentrate (WCFC) powder increased blood levels of brain derived neurotrophic factor (BDNF) during the first 60 minutes after ingestion. In the present report, we performed a single dose, placebo-controlled, within-subject study to confirm and further investigate this effect. Twenty healthy subjects with ages ranging from 25 to 35 participated in this study. All fasted and resting subjects received placebo on Day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Various genes are involved in obesity phenotypes like PCSK1, MCR4, BDNF and POMC. 39,[78][79][80][81][82][83] FTO was one of the six genes missed in fused toe mice on the 1.6-Mb chromosome segment, therefore it is rational to determine the FTO deficient phenotype (Figure 1). The mutation in these genes induced abnormal facial structure features, fused digits, abnormal left-right asymmetry and underdevelopment of hypothalamus and hyperplasia of thymus.…”
Section: Defi Cien C Y and Mutati On Of F Tomentioning
confidence: 99%
“…Various genes are involved in obesity phenotypes like PCSK1, MCR4, BDNF and POMC. 39,[78][79][80][81][82][83] FTO was one of the six genes missed in fused toe mice on the 1.6-Mb chromosome segment, therefore it is rational to determine the FTO deficient phenotype (Figure 1). The mutation in these genes induced abnormal facial structure features, fused digits, abnormal left-right asymmetry and underdevelopment of hypothalamus and hyperplasia of thymus.…”
Section: Defi Cien C Y and Mutati On Of F Tomentioning
confidence: 99%
“…Many genes that control the same phenotypes with lipid storage and obesity have been identified, such as PCSK1 108 , 109 , MCR4 110 - 112 , BDNF 113 , and POMC 114 - 116 . Therefore, it was reasonable to determine the phenotype of FTO deficiency.…”
Section: Deficiency and Mutation Of Fto In Human/micementioning
confidence: 99%
“…Whole coffee cherry extract (WCCE), is a proprietary, safe [8], powdered extract of whole coffee cherries from Coffea arabica with high levels of polyphenols and substantially low (<2%) levels of caffeine (for a detailed composition profile, please see Table 1 of the study by Reyes-Izquierdo et al (2013b) [9]). WCCE has been previously associated with increased serum concentrations of both circulating and exosomal brain-derived neurotrophic factor (BDNF), in addition to increased alertness and decreased fatigue [4,[9][10][11][12]. BDNF is a protein synthesized in neurons and other types of cells, and it is associated with a range of neural (e.g., plasticity) [13][14][15][16] and psychological processes [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…MCI is marked by problems with memory, language, thinking, and judgment that are greater than normal age-related changes. Given that earlier studies reported that WCCE may stimulate increases in BDNF [9,11], one remaining question was whether WCCE, potentially through increases in BDNF, could acutely improve cognitive function or provide protective effects in older adults who may be on the verge of or have MCI. To this end, BDNF has been associated with such changes via its effects on N-methyl-D-aspartate-type (NMDA) receptors [32][33][34].…”
Section: Introductionmentioning
confidence: 99%